Social Disadvantages of Ease of Transactions Using Blockchain - Meng Sopheara; Chhoub Sotharith (Journal of Management and Administration Provision, 2022)
A distributed, immutable record like that provided by blockchain technology has the ability to greatly streamline and fortify financial transactions while also reducing associated risks. Blockchain transactions are simple, but this convenience comes at a social cost. The concentration of wealth in the hands of a few would be a potential drawback, as would be the possibility of a blockchain's centralization. The anonymity of blockchain transactions also makes them conducive to unlawful operations like money laundering and the selling of illicit items. Finally, the energy consumption essential to a blockchain network's operation raises environmental problems.